Bisphenols: More unnecessary surprises. (1st January 2016) - Thayer, Kristina A.; Pelch, Katie E.; Birnbaum, Linda S.; Bucher, John R.
ABSTRACT: A recent biomonitoring study "Bisphenol A, Bisphenol S, and 4-Hydroxyphenyl 4-Isoprooxyphenylsulfone (BPSIP) in Urine and Blood of Cashiers" reported on levels of BPA, BPS, and a novel BPS-derivative (BPSIP) in cashiers compared to non-cashiers. Our study was the first to detect BPSIP in humans. In this commentary we discuss our findings in the context of considering bisphenols as a class in health assessments and how technological advances in exposure assessment could be utilized to more efficiently identify emerging chemicals of interest.